Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.17219/acem/98952
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between glycemic index and glycemic load of diets and nutritional status and antioxidant/oxidant status in the serum of patients with lung cancer

Abstract: Zabłocka-Słowińska KA, Skórska K, Płaczkowska S, et al. The relationships between glycemic index and glycemic load of diets and nutritional status and antioxidant/oxidant status in the serum of patients with lung cancer. Abstract Background.A low glycemic index (GI) and glycemic load (GL) of diets as well as proper nutritional status may partially slow down depletion in antioxidant capacity, and may therefore have an impact on antioxidant/ oxidant status in lung cancer patients. However, no studies concerning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…It has been widely demonstrated that healthy diets and physical activity have beneficial effects in several pathological conditions including cancer [55,56]. Several studies have highlighted how some foods with a high glycemic index or inflammatory index are associated with chronic inflammation, and in turn, to a plethora of inflammatory-related diseases including cancer, diabetes, and cardiovascular diseases [57,58]. Indeed, nutrients can directly or indirectly modulate the molecular and physiological mechanisms responsible for cell proliferation, differentiation, and programmed cell death.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely demonstrated that healthy diets and physical activity have beneficial effects in several pathological conditions including cancer [55,56]. Several studies have highlighted how some foods with a high glycemic index or inflammatory index are associated with chronic inflammation, and in turn, to a plethora of inflammatory-related diseases including cancer, diabetes, and cardiovascular diseases [57,58]. Indeed, nutrients can directly or indirectly modulate the molecular and physiological mechanisms responsible for cell proliferation, differentiation, and programmed cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Total oxidant status (TOS) was measured in serum using the earlier described method [ 20 ], in which the oxidants present in the sample oxidize the ferrous ion-o-dianisidine complex to ferric ion (o-dianisidine dihydrochloride, ref. No: D3235; ammonium iron (II) sulfate hexahydrate, ref.…”
Section: Methodsmentioning
confidence: 99%
“…Mobile phase was composed of 0.2% trifluouroacetic acid in methanol. External standards of gallic acid, protocatechuic acid, 4‐hydroxybenzoic acid, syringic acid, p ‐coumaric acid, and ferulic acid were used for the identification and quantification (Zabłocka‐Słowińska et al., 2019).…”
Section: Methodsmentioning
confidence: 99%